1995
DOI: 10.1104/pp.107.3.719
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Herbicides (Specific Inhibitors of Imidazoleglycerol Phosphate Dehydratase)

Abstract: A new mode of herbicidal action was established by finding specific inhibitors of imidazoleglycerol phosphate dehydratase, an enzyme of histidine (His) biosynthesis. Three triazole phosphonates inhibited the reaction of the enzyme with Ki values of 40 f 6.5, 10 f 1.6, and 8.5 2 1.4 nM, respectively, and were highly cytotoxic to cultured plant cells. This effect was completely reversed by the addition of His, proving that the cytotoxicity was primarily caused by the inhibition of His biosynthesis. These inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Initial rates were measured in triplicate, and kinetics parameters were obtained by calculating the experimental data using a GraFit program (Erithacus Software, Middlesex, UK). Inhibition by IRL 1803 and 3-amino-1,2,4-triazole was studied as described previously (Mori et al, 1995). One unit of enzyme activity was defined as the amount of enzyme catalyzing the formation of 1 pmol of IAP/min.…”
Section: Kinetics Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Initial rates were measured in triplicate, and kinetics parameters were obtained by calculating the experimental data using a GraFit program (Erithacus Software, Middlesex, UK). Inhibition by IRL 1803 and 3-amino-1,2,4-triazole was studied as described previously (Mori et al, 1995). One unit of enzyme activity was defined as the amount of enzyme catalyzing the formation of 1 pmol of IAP/min.…”
Section: Kinetics Studiesmentioning
confidence: 99%
“…It is also known that 3-amino-l,2,4-triazole inhibits catalase (Smith, 1985). On the other hand, we have recently synthesized a triazole derivative as a new IGPD inhibitor, IRL 1803, and reported that it exhibits remarkable phytotoxic effects in basil cell culture (Mori et al, 1995). The phyotoxicity was completely reversed by the addition of His (Mori et al, 1995).…”
mentioning
confidence: 97%
See 3 more Smart Citations